The Deregulation of US Financial Markets as a Cause of Their Crisis - Schiman, Stefan (Momentum Quarterly, 2017)
Financial market reforms in the wake of the Great Depression of the 1930s and the reshaping of the international financial system in Bretton Woods 1944 laid the foundations of a market-based economic framework with highly regulated financial markets that was established in the Western hemisphere after the Second World War. The instability of the exchange rate regime due to the asymmetric role of the dollar led to the breakdown of this regulatory framework. Strong exchange rate volatility was followed by oil price shocks which gave rise to a policy of high interest rates that undermined financial market regulation in the USA. The demand-oriented macroeconomic policy, no longer sustainable after the oil crisis, was superseded by a neo-liberal doctrine that provided the theoretical underpinning to the deregulation process. Its implicit competitive stance put pressure on sheltered financial services and their profitability, leading to a wave of mergers in the financial sector; these large financial groups were able to embark on ever more risky operations that were closely entangled with the deposit and loan business. This mixture, akin to the origins of the financial market crisis of 1929, ignited with the real estate price boom in the USA and triggered the financial market crisis of 2007-08.